analisis Analisis efektivitas manajemen strategi koperasi syariah di indonesia - Agustina, Nurlaila Tria (Maliki Interdisciplinary Journal, 2025)
Sharia cooperatives play a strategic role in empowering the community’s economy and enhancing welfare through Islamic economic principles, deliberation (musyawarah), transparency, and fairness. This study analyzes the effectiveness of strategic management and capacity-building assistance in Sharia cooperatives, focusing on internal and external factors, digital transformation, and product and service innovation. The results indicate that continuous mentoring improves cooperative performance, expands marketing networks, strengthens institutional resilience, and enhances member welfare. These findings highlight the importance of responsive managerial strategies and Sharia financial literacy in building competitive and sustainable Sharia cooperatives. The implications of this research provide theoretical contributions by enriching the capacity development model for nonprofit organizations, particularly in the context of Islamic economics. Practically, these findings serve as guidance for cooperative administrators, the Cooperatives Office, and supporting institutions in designing more measurable and effective empowerment programs. By adopting the proposed strategies, Islamic cooperatives are expected to transform into more resilient, innovative business entities with a broad impact on improving the welfare of their communities.